Mirko Kujačić and Social Art in Serbia - Marković, Srdjan D.; Vukotić Lazar, Marta M. (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
The art of the fourth decade of the twentieth century which, as if it was announcing the World War II, was polarized between so-called “pure art” (l’art pour l’art), engaged art (l’art pour l’idee), and war realism. This separation often caused ideological conflicts that were intensifying and spreading into the sphere of political conflicts. Two models of the leftist ideological concepts are reflected into the socially engaged artistic work of the two programmatically declared groups, which were devoted to an engaged form of artistic activity: the group “Earth” (1929 – 1935) from Zagreb and the group “Life” (1932 – 1940) from Belgrade. Social art in Serbia had strong foundations in the second half of the third decade of the twentieth century and stretched throughout the period of war events until 1943. In the period between the two world wars it started with The Manifest of Mirko Kujačić, (1901 – 1987) published in 1932 and an exhibition of his surrealistic collages, framed shoes, an object named The Winter Motif and its counterpart, the painting named The Root of Belgrade Gentility. An important event for the continuation of such artistic tendencies was the forming of the group Life in 1934 in Belgrade, with Kujačić as one of the founders and the main protagonist.
Keywords: Yugoslav modern art; social art; graphics; painting; “Life”; “Earth”; “Serbia”